Recovery of fat snook, Centropomus parallelus (Teleostei: Perciformes) after subchronic exposure to copper - Oss, Rodrigo Nunes; Baroni, Vinícius Dadalto; Duarte, Rafael Mendonça; Val, Adalberto Luis; Val, Vera Maria Fonseca Almeida e; Gomes, Levy de Carvalho (Comparative Biochemistry and Physiology - C Toxicology and Pharmacology, 2013)
We studied the recovery of juvenile fat snook (Centropomus parallelus) after subchronic exposure to different concentrations of copper. Healthy juveniles (1.98 g) were exposed to 25 or 50 μg Cu/L for 30 days (12 replicates with 5 fish in each one), and recovery was observed at 0, 4, 10, and 30 days after exposure (3 replicates with 5 fish in each one). Copper genotoxicity in exposed individuals was observed using a micronucleus assay, and recovery was not observed even 30 days post-exposure. Copper accumulation was observed in fish exposed to 25 or 50 μg/L of copper in the gills (14.4 and 34.4 μg/g, respectively) and muscle (5.7 and 5.5 μg/g, respectively), and a return to normal copper levels (6.0 μg/g for gills and 2.5 μg/g for muscle) was observed 4 and 30 days post-exposure in the gills and muscle tissues, respectively. Glutathione S-transferase (GST) was 80% inhibited in individuals exposed to copper and returned to normal levels for fish exposed to basal concentrations within 10 days. Although copper accumulation in tissues dispersed 30 days post-exposure, no recovery from genotoxicity was observed during this time. Thirty days was not enough to recover juvenile fat snook following subchronic exposure to copper. © 2013 Elsevier Inc.
Keywords: Copper; Fresh Water; Glutathione Transferase; Animals Experiment; Centropomus Parallelus; Controlled Study; Genotoxicity; Gill; Micronucleus; Micronucleus Test; Muscle; Nonhuman; Perciformes; Priority Journal; Water Quality